Primary recovery of carboxymethyl cellulase from Thermophilic Bacillus licheniformis 2d55 using an aqueous two-phase system - Kazeem, Muinat Olanike; Abbasiliasi, Sahar; Shun, Tan Joo; Baharuddin, Azhari Samsu; Abdul Rahman, Nor’ Aini (Universiti Putra Malaysia Press, 2025)
This study uses an aqueous two-phase system developed from a polymer and salt to purify a thermostable carboxymethyl cellulase (CMCase) produced by thermophilic Bacillus licheniformis 2D55. The effects of system parameters, such as polyethene glycol (PEG) molar mass, salt concentration, crude load, NaCl concentration and pH on partitioning and recovery efficiency, are evaluated. Sodium dodecyl sulphate polyacrylamide gel electrophoresis (SDS-PAGE) is used to determine the purity of the CMCase. The enzyme is successfully purified, achieving a 10.9-fold purification and 86.62% yield. The maximum purification condition is achieved in ATPS comprising 20.5% PEG 8000/15% sodium citrate, with a crude load of 17% (w/w), NaCl of 1.0% (w/w) and pH at 7.0. Under these conditions, a partition co-efficient of 0.21 is observed, indicating that CMCase preferentially partitions to the bottom phase. These results demonstrate the potential of ATPS for the purification of thermostable CMCase from the fermentation broth of thermophilic Bacillus licheniformis 2D55.